Proactive Risk Assessment for Ebola-Infected Patients: A Systematic Approach to Identifying and Minimizing Risk to Healthcare Personnel. (26th May 2016) - Fernandez, Rosemarie; Mitchell, Steven; Ehrmantraut, Ross; Meschke, John Scott; Simcox, Nancy J.; Wolz, Sarah A.; Parker, Sarah Henrickson
Abstract : Performing patient care while wearing high-level personal protective equipment presents risks to healthcare providers. Our failure mode effects analysis identified 81 overall risks associated with providing hygienic care and linen change to a patient with continuous watery stool. Implementation of checklists and scheduled pauses could potentially mitigate 76.5% of all risks. Infect Control Hosp Epidemiol 2016;37:867–871